The Qingming festival / Ong Sheau Fen - Ong, Sheau Fen (Academy of Language Studies, 2023)
The Qingming Festival, also known as Tomb Sweeping Day or Ancestors' Day, is one of the most important festivals celebrated by the Chinese. This year, the Qingming Festival falls on April 5th. One of the most important rituals performed during the Qingming Festival is the practice of tomb sweeping. This is when people clean and tidy up the tombs, graveyards, and columbariums of their ancestors and deceased relatives and pay homage to them. When visiting graves, visitors will bring Qingtuan as a snack. Qingtuan, which means "green rice ball," is made from the juice of green-colored wormwood and sticky rice. In ancient times, people believed that wormwood could ward off evil spirits, making it a suitable snack for grave-visiting. During the Qingming Festival, people also go for walks in the countryside because it is spring when everything starts to grow, and the scenery is stunning. When out for a spring outing, many people like to fly kites. In the past, after flying kites high up into the sky, it was popular to cut the string and let go of the kite. It was believed doing this could cure illnesses and ward off disasters, bringing good luck to oneself.